KELAYAKAN FINANSIAL REPLANTING TANAMAN KARET DI DESA BATUMARTA 1 KECAMATAN LUBUK RAJA KABUPATEN OGAN KOMERING ULU PROVINSI SUMATERA SELATAN - Tiara Naisyah; Bambang Sumantri; Nusril Nusril (Jurnal Agrisep)
This research aim to: 1) to analyze the amount of financial worthiness of rubber plantation as long as economic age in Batumarta 1 Lubuk Raja Ogan Komering Ulu regency. 2) To know the level of sensitivity in replanting rubber to several dominant factors related to finance and advantage in Batumarta 1 Lubuk Raja Ogan Komering Ulu regency. 77 respondents are chosen, about 30 % from 258 population which have represented population, because the population in Batumarta1 homogeneously relative in rubber plantation system, that is rejuveration system. The sample was chosen by using Simple Random Sampling Method. The research methodology is Survey. While the data is analyzed by worthiness count criteria which consist of Net B/C ratio, Gross B/C ratio, Provitability ratio, Net Present value (NPV), Internal Return Rate(IRR), this valuation done to know the worthiness off rubber replanting. Otherwise, also done the counting of sensitivity experimental. The result shows that rubber replanting in Batumarta 1 can be properly applied and the most sensitive factor is the decresing of selling price, increasing of production cost (fertilizer and total cost before tax)